2015
DOI: 10.1007/s11420-015-9453-9
|View full text |Cite
|
Sign up to set email alerts
|

Initial Surgical Treatment of Humeral Shaft Fracture Predicts Difficulty Healing when Humeral Shaft Nonunion Occurs

Abstract: Background: Although most humeral nonunions are successfully treated with a single procedure, some humeral nonunions are more difficult to heal and require multiple procedures. Current literature does not provide evidence describing how the prognosis for surgical repair in patients who develop humeral diaphyseal nonunions may be affected by initial operative versus nonoperative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…As most patients showed varying degree of misalignment, implant broken and/or loosen, or pseudarthrosis, use of LCP xation could achieve a high degree of cortex-to-cortex stability with compression of the bone segments and correction of the deformities for those cases. Also, repeated prior surgeries might result in a poor biological environment for fracture repair in cases during this study, this is consistent with the founding of Konda et al [30], where humeral shaft nonunions following initial operative xation of the index fracture were more resistant to achieving union when compared to nonunions forming after initial non-operative treatment. And they recommended plate xation and bone graft for recalcitrant humeral shaft nonunion.…”
Section: Discussionsupporting
confidence: 90%
“…As most patients showed varying degree of misalignment, implant broken and/or loosen, or pseudarthrosis, use of LCP xation could achieve a high degree of cortex-to-cortex stability with compression of the bone segments and correction of the deformities for those cases. Also, repeated prior surgeries might result in a poor biological environment for fracture repair in cases during this study, this is consistent with the founding of Konda et al [30], where humeral shaft nonunions following initial operative xation of the index fracture were more resistant to achieving union when compared to nonunions forming after initial non-operative treatment. And they recommended plate xation and bone graft for recalcitrant humeral shaft nonunion.…”
Section: Discussionsupporting
confidence: 90%
“…Firstly, plate xation is the most widely used method for long bone xation due to economic constraints and surgeons' preference in China, and as most patients in this study showed varying degrees of misalignment or pseudarthrosis, the use of LCP xation could achieve a high degree of cortex-to-cortex stability with compression of the bone segments while correcting deformities. Secondly, repeated prior surgeries might result in a poor biological environment for fracture repair in cases in this study, a second plate xing vertically to the anterior of the bone graft for structural support could maintain intimate contact between the bone graft and both nonunion segments, maximizing osteoconductive, osteogenic and osteoinductive properties of autologous bone, this is consistent with the founding of Konda et al [30], where humeral shaft nonunions following initial operative xation of the index fracture were more resistant to achieving union when compared to nonunions forming after initial non-operative treatment. And they recommended plate xation and bone graft for recalcitrant humeral shaft nonunion.…”
Section: Discussionsupporting
confidence: 87%
“…One study reported a healing rate of 97% for anterior augmentation plating of aseptic humeral shaft nonunion [ 28 ], and a review of 36 studies found that plating with autologous bone grafting achieves a union rate of up to 98% in patients with humeral shaft nonunion [ 29 ]. Furthermore, plate fixation and bone grafting is recommended for recalcitrant humeral shaft nonunion following initial operative fixation of the index fracture [ 30 ]. In the present study, double plate fixation combined with autologous iliac crest structural bone grafting achieved excellent or good outcomes in patients with recalcitrant humeral shaft nonunion after prior failed surgeries.…”
Section: Discussionmentioning
confidence: 99%